Avaliação sazonal de Carotenóides provitamina A (alfa- e beta caroteno) e vitamina E ( alfa- tocoferol) em macroalgas marinhas pertencentes ao gênero Cryptonemia - Nascimento, Rômulo Malta (2009)
The objective of this research project was to investigate the existence of seasonal variation of both provitamin A carotenoids ( and carotene) and vitamin E ( and tocopherol) in two species of red marine macroalgae, Cryptonemia luxurians and C. crenulata. The alga samples were collected monthly from January to December of 2007, during the low tides of Pacheco Beach, Caucaia, Ceará. The alga samples were dehydrated at 40°C for 15 h. The dried alga material was crushed into a fine powder and then submitted into the procedures of extraction with methanol, saponification with potassium hydroxide and partition with n-hexane. For simultaneous analyses of carotenoids and tocopherols the HPLC system consisted of a Waters Spherisorb-Hichrom S5 ODS-2 (4.6 x 250 mm) column and a mobile phase of MeOH: THF (95:5, v/v), delivered at 1.5 mL min -1 , with detection at 450 nm and 292 nm, respectively. In both species belonging to the genre Cryptonemia were detected  and carotene throughout all the sampling months. In general, both species contained larger concentrations of carotene than carotene. Despite the macroalgae analyzed belonged to the same genre, it was possible to verify a variation in the concentrations of provitamin A carotenoids throughout the year. C. luxurians was elected as a better source of vitamin A than C. crenulata. Among the isomers of vitamin E, tocopherol showed the higher concentrations. C. luxurians showed the highest levels of both tocopherols. According to these results, C. luxurians and C. crenulata oven-dried at 40°C for 15 h are possibly better sources of vitamin E than vitamin A. To verify the seasonal behavior of the concentrations of provitamin A carotenoids and vitamin E, grouping analysis was utilized. Based upon the results of this analysis it was established that tocopherol concentrations showed a more substantiated variation in the macroalgae within the seasons of the year as well as among the two species. On the other hand, the provitamin A carotenoids, exhibited more stable concentrations considering the species and the seasons. Nevertheless, only with subsequent studies it will be possible to determine the factors and its influence on the variation of provitamin A carotenoids and vitamin E contents of the analyzed species.